THE EFFECT OF THE PERPA METHOD, SOPHISTICATED INVESTORS, AUDIT QUALITY ON PROFIT MANAGEMENT IN MANUFACTURING COMPANIES REGISTERED ON THE IDX IN 2016-2021 - Windasari Rachmawati; Naini Rizka Amalia; Johanis Souisa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze and find empirical evidence on earnings management practices, especially in the manufacturing sector in Indonesia. Most companies in Indonesia are controlled by family business companies. For that what about sophisticated investors. This study has a target finding to identify the existence of earnings management practices in manufacturing companies in Indonesia. The sample used in this research is a manufacturing company listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2021. The data analysis method for this research uses multiple linear regression analysis. The independent variables in this study are the independent variables in this study consisting of PERPA, Sophisticated Investors, Audit Quality. Meanwhile, the dependent variable in this study is Earning Management, which is proxied by the value of discretionary accruals from the Modified Jones Model. The control variable used is the ratio of firm size and profitability. Based on a sample of 410 issuers for 6 years of observation that have fulfilled all stages of assumptions in multiple regression testing, it resulted in a decision that the PERPA and Sophisticated Investor variables had no effect on earnings management practices. While the audit quality variable affects earnings management. Earnings management control variable that uses the level of size or company size has a negative and significant effect on earnings management actions, while the other control variable, namely profitability, has no effect on earnings management (eanings management).